VD_FINDINFO HC / 2011 / 698 vom 16. Dezember 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, DIVORCE, AUTONOMIE, QUI PEUT ETRE RAISONNABLEMENT EXIGÉ | 176 al. 1 ch. 1 CC, 179 CC, 308 al. 1 CPC